The Influence of Financial Literacy, Ease of Use, and Risk Perception on the Intention to Use E-Wallet (LinkAja): A Case Study of the Telukjambe Timur Community - Nurrisma Rahayu; Sihabudin Sihabudin; Robby Fauji (International Journal of Economics and Management Research, 2025)
This study aims to analyze the influence of financial literacy, ease of use, and risk perception on public interest in using the LinkAja e-wallet service in Telukjambe Timur District, Karawang Regency. A quantitative approach with a descriptive-verificative method was employed to assess the relationships among the variables. Primary data were collected through structured questionnaires distributed to 100 respondents selected through purposive sampling techniques. The selection criteria focused on individuals who have at least heard of or used LinkAja, ensuring the relevance of their responses to the research objectives. Data were analyzed using multiple linear regression with the support of SPSS version 26 software. The findings reveal that, simultaneously, the three independent variables—financial literacy, ease of use, and risk perception—significantly influence public interest in adopting LinkAja. However, on a partial basis, only ease of use and risk perception exert a statistically significant effect. In contrast, financial literacy does not show a meaningful impact. This implies that while having knowledge about financial tools is beneficial, it is not the decisive factor in motivating individuals to use digital wallets like LinkAja. Ease of use proves to be a major determinant, as users tend to prefer platforms that are intuitive and user-friendly. Risk perception also plays a critical role, where lower perceived risks enhance user trust and willingness to engage in digital transactions. Based on these findings, it is recommended that LinkAja prioritize user experience improvements and continuously invest in robust cybersecurity measures to build user confidence and broaden adoption across demographic segments.